Increasing mother’s knowledge through “Isi Piringku” education as an effort to prevent stunting among toddlers in Sungai Tuan Ulu Village, Banjar Regency - Filia Sofiani Ikasari; Iis Pusparina; Dewi Irianti (Universitas Muhammadiyah Magelang, 2022)
Banjar Regency in South Kalimantan Province ranks first for the Regency with a significant increase in stunting cases. One of the government's efforts to prevent stunting is to promote education about